Exit timing of venture capitalists in the course of an initial public offering - Neus, Werner; Walz, Uwe (Journal of Financial Intermediation, 2005)
We analyze the disinvestment decisions of venture capitalists in the course of an IPO of their portfolio firms. The capital market learns of the project quality only in the period following the IPO. Venture capitalists with high-quality firms must choose between immediately selling their stake in the venture at a price below the true value and waiting until the true value is revealed. We show that this choice is facilitated by a reputation-based mechanism in a repeated-game setting. This allows us to explain the phenomenon of “hot-issue market behavior” involving early disinvestments and a high degree of price uncertainty. In a further step, we provide a new rationale for underpricing. We show that young venture capitalists may use underpricing as a device for credibly committing themselves to establishing reputation.